Exploring career realities: elevating graduate employability through job shadowing - Hanaliza Kamis; Phan, Jasmine Ah Kiaw; Sheela Karunaharan Thanaraj; Jen, Ling Gan (Penerbit Universiti Kebangsaan Malaysia, 2024)
Many students in higher education institutions face significant challenges in bridging the gap between theoretical knowledge and practical application within real-world work environments. The Job Shadowing program aims to provide participants with an immersive glimpse into the daily operations of different jobs and workplaces, offering invaluable insights into real-world work environments. As part of the program, students engage with startup companies for a total of eight hours, have the chance to observe firsthand how these businesses function and are tasked with a project to address. Upon completion, students present their findings to the organizations, then receive valuable feedback. The program's effectiveness is assessed and compared through pre- and post-program tests. It revealed a significant improvement with 60% of participating students demonstrating enhanced test scores. Overall, the performance of program participants surpassed that of their non-participating peers, underscoring the program’s impact on bridging the gap between academic theory and practical application.